Unlocking Musical Brilliance: How Traditional Talempong Pacik Music Enhances the Intelligence of Children Aged 5-6 Years - Tiara Wulandari; Jhoni Warmansyah; Wahidah Fitriani; Restu Yuningsih; Meliana Sari; Abdul Kadir Naffari (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to determine the effect of playing the traditional musical instrument Talempong Pacik on the musical intelligence of children aged 5-6 years. The research employs a quantitative approach using an experimental method. The sample consists of 21 children selected through simple random sampling. Data collection techniques include observation sheets to assess the development of children's musical intelligence. Data analysis is conducted using a t-test. The results show a significant influence of playing the traditional musical instrument Talempong Pacik on the musical intelligence of children aged 5-6 years, with a tÔéÆ value greater than t_t (39.28 > 2.08), leading to the rejection of the null hypothesis (hÔéÇ) and acceptance of the alternative hypothesis (hÔéü). This indicates that playing the traditional musical instrument Talempong Pacik can be an effective means of supporting learning to develop children's musical intelligence.